(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Internet of things (IoT) has wide applications; one of which is flood monitoring and coordinating. Impera tiveness sensibility methodologies can be reproduced in IoT, which can alleviate both essentialness draining and human un dertakings legitimate to complete the obligation. In India, there are no vigilant techniques for the opening of dam gates or when there is huge probabilities arise in floods. The exist ing procedure in India is physical which one of the major is sues is. Because of the unexpected lifting of gates of the dam villages surrounding that area are extremely influenced and cause to death of the public. This impact on the survival of the public at many times. The suggested system is a defined as the process that can be installed in the dam’s catchment re gions and will serve as a watchful module that will alert the public to the condition of the dam’s gates and even the water level at the dam’s gates. The proposed system consists of Dam storage information, Temperature levels & Humidity levels and SMS vigilant module, public information system. A web application is designed for efficient utilization of the proposed system which will indicate the position of gates all over the dams in India.